2004
DOI: 10.1242/dev.00949
|View full text |Cite
|
Sign up to set email alerts
|

The role ofJAGGEDin shaping lateral organs

Abstract: Position-dependent regulation of growth is important for shaping organs in multicellular organisms. We have characterized the role of JAGGED, a gene that encodes a protein with a single C2H2zinc-finger domain, in controlling the morphogenesis of lateral organs in Arabidopsis thaliana. Loss of JAGGED function causes organs to have serrated margins. In leaves, the blade region is most severely affected. In sepals, petals and stamens, the strongest defects are seen in the distal regions. By monitoring cell-cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
324
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(343 citation statements)
references
References 46 publications
(43 reference statements)
11
324
0
8
Order By: Relevance
“…Leafy petioles are also caused by the ectopic expression of LEAFY PETIOLE (LEP), which encodes an EREBP/AP2-type transcription factor (van der Graaff et al, 2000), and JAGGED (JAG), which encodes a C 2 H 2 zinc finger transcription factor (Dinneny et al, 2004;Ohno et al, 2004). One possibility is that BOP activity regulates the spatial expression of leaf-promoting transcription factors such as JAG or LEP in the proximal parts of leaves and in floral bracts.…”
Section: Bop and Proximal-distal Leaf Patterningmentioning
confidence: 99%
See 2 more Smart Citations
“…Leafy petioles are also caused by the ectopic expression of LEAFY PETIOLE (LEP), which encodes an EREBP/AP2-type transcription factor (van der Graaff et al, 2000), and JAGGED (JAG), which encodes a C 2 H 2 zinc finger transcription factor (Dinneny et al, 2004;Ohno et al, 2004). One possibility is that BOP activity regulates the spatial expression of leaf-promoting transcription factors such as JAG or LEP in the proximal parts of leaves and in floral bracts.…”
Section: Bop and Proximal-distal Leaf Patterningmentioning
confidence: 99%
“…Haughn, unpublished results). Plants misexpressing JAG also develop floral bracts (Dinneny et al, 2004;Ohno et al, 2004), another aspect of the bop1 bop2 mutant phenotype. Previous analyses of bop1-1 plants have shown that knox genes are also misexpressed in the leaves, predominantly in the petiole region (Ha et al, 2003).…”
Section: Bop and Proximal-distal Leaf Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have reported alteration of leaf form via gene manipulation, the majority of these investigations have utilized upstream regulators of development (e.g. transcription factors and hormonal signalling systems), making it difficult to define the actual downstream growth processes involved in generating the observed morphogenic response (Autran et al, 2002;Nath et al, 2003;Palatnik et al, 2003;Dinneny et al, 2004). Testing the hypothesis that growth repression could play a role in leaf morphogenesis requires the use of factors that are much closer to the final downstream effectors of growth.…”
Section: Introductionmentioning
confidence: 99%
“…Petal primordia arise at four loci in the second whorl, and this positioning is established independently of the process that determines organ identity (Griffith et al, 1999;Brewer et al, 2004;Takeda et al, 2004;Xing et al, 2005;Lampugnani et al, 2013). After initiation, the growth of petals depends on the activity of cell division and expansion along the proximal-distal axis, which is partly regulated by JAGGED (Dinneny et al, 2004;Ohno et al, 2004). Final petal size is determined by the balance of cell proliferation and expansion (Mizukami and Fischer, 2000;Szécsi et al, 2006).…”
mentioning
confidence: 99%